Inhibition of placental mTOR signaling provides a link between placental malaria and reduced birthweight. Issue 1 (December 2017) - Dimasuay, Kris; Aitken, Elizabeth; Rosario, Fredrick; Njie, Madi; Glazier, Jocelyn; Rogerson, Stephen; Fowkes, Freya; Beeson, James; Powell, Theresa; Jansson, Thomas; Boeuf, Philippe
Abstract Background PlacentalPlasmodium falciparum malaria can trigger intervillositis, a local inflammatory response more strongly associated with low birthweight than placental malaria infection alone. Fetal growth (and therefore birthweight) is dependent on placental amino acid transport, which is impaired in placental malaria-associated intervillositis. Here, we tested the hypothesis that mechanistic target of rapamycin (mTOR) signaling, a pathway known to regulate amino acid transport, is inhibited in placental malaria-associated intervillositis, contributing to lower birthweight. Methods We determined the link between intervillositis, mTOR signaling activity, and amino acid uptake in tissue biopsies from both uninfected placentas and malaria-infected placentas with and without intervillositis, and in an in vitro model using primary human trophoblast (PHT) cells. Results We demonstrated that (1) placental mTOR activity is lower in cases of placental malaria with intervillositis, (2) placental mTOR activity is negatively correlated with the degree of inflammation, and (3) inhibition of placental mTOR activity is associated with reduced placental amino acid uptake and lower birthweight. In PHT cells, we showed that (1) inhibition of mTOR signaling is a mechanistic link between placental malaria-associated intervillositis and decreased amino acid uptake and (2) constitutive mTOR activation partially restores amino acid uptake. Conclusions Our data support the concept that inhibition of placental mTOR signaling constitutes a mechanistic link between placental malaria-associated intervillositis and decreased amino acid uptake, which may contribute to lower birthweight. Restoring placental mTOR signaling in placental malaria may increase birthweight and improve neonatal survival, representing a new potential therapeutic approach.